2020
DOI: 10.1371/journal.pone.0230770
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of peer counseling, social engagement, and combination interventions in improving depressive symptoms of community-dwelling Filipino senior citizens

Abstract: Introduction Little is known about community-based interventions for geriatric depression in low-resource settings. This study assessed the effectiveness of 3-month-duration interventions with peer counseling, social engagement, and combination vs. control in improving depressive symptoms of community-dwelling Filipino senior citizens. Methods We conducted an open (non-blinded), non-randomized trial of senior citizens at risk for depression. Three different 3-month interventions included peer counseling (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 48 publications
1
61
0
1
Order By: Relevance
“…Namely, SC partly affected depressive symptoms by sleep quality among the T2DM patients. Besides, except for sleep quality, there are other possible mechanisms between SC and depression, like social engagement ( 48 ), loneliness ( 49 ), life satisfaction ( 50 ), and traumatic life experience ( 51 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, SC partly affected depressive symptoms by sleep quality among the T2DM patients. Besides, except for sleep quality, there are other possible mechanisms between SC and depression, like social engagement ( 48 ), loneliness ( 49 ), life satisfaction ( 50 ), and traumatic life experience ( 51 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…At the 12th month, overall Quality of life, sensory ability, social participation, intimacy, social support, and perception of health care from family members significantly improved. Depression was also reduced at the 12th month Other/Multi-component Abdi et al (2019) [ 25 ] a religion-spiritual program that included strategies such as reading verses from the Holy Quran and spiritual caring services Iran Randomised control trial 100 Older adults with cardiovascular disease from Mostafa–Khomini hospital having a religion of Islam-Shia, 50 older adults in each group Six educational sessions, each in a week and lasted about 30–45 min No intervention BDI– depression; LSI-Z—Life satisfaction 3 months Higher mean life satisfaction scores and lower mean depression scores in intervention group than control group post intervention Carandang et al(2020) [ 43 ] Peer counselling group: Peer counsellors performed 1-h home visits weekly to their assigned clients Social engagement group: Senior citizens joined 3-h weekly social events held at the OSCA Center Combination group: both peer counselling and social engagement interventions Philippines 4-arm quasi-experimental, controlled study 270 community-dwelling Filipino senior citizens with mean age was 68.3 years, who had tendency towards depression based on the 15-item Geriatric Depression Scale. peer counselling ( n = 65), social engagement ( n = 66), and combination ( n = 65) and control group ( n = 68) 3 months usual or standard care from health and aged care services GDS—Depression.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by an extensive body of literature. A recent study found that peer counselling, a certain interactive process, was effective in improving depressive symptoms, psychological resilience and social support amongst Filipino senior citizens (Carandang et al., 2020). Buman et al also reported that trained peer volunteers might enhance long‐term maintenance of physical activity with older adults (Buman et al., 2011).…”
Section: Discussionmentioning
confidence: 99%